2020
DOI: 10.1371/journal.pone.0232115
|View full text |Cite
|
Sign up to set email alerts
|

Design of a new multiplex PCR assay for rice pathogenic bacteria detection and its application to infer disease incidence and detect co-infection in rice fields in Burkina Faso

Abstract: Crop diseases are responsible for considerable yield losses worldwide and particularly in sub-Saharan Africa. To implement efficient disease control measures, detection of the pathogens and understanding pathogen spatio-temporal dynamics is crucial and requires the use of molecular detection tools, especially to distinguish different pathogens causing more or less similar symptoms. We report here the design a new molecular diagnostic tool able to simultaneously detect five bacterial taxa causing important dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…When assessing the PCR detection limit of each marker individually, it was observed that XEA5 lowered the limit of detection value to 10 pg/µL, indicating that the sensitivity of the simplex PCR targeting XEA5 marker is ten-fold higher than the multiplex PCR. The detection limit of 0.1 ng/µL attained for the multiplex PCR is similar to what has been reported in other studies (0.02 and 0.5 ng/µL) [40,41].…”
Section: Discussionsupporting
confidence: 89%
“…When assessing the PCR detection limit of each marker individually, it was observed that XEA5 lowered the limit of detection value to 10 pg/µL, indicating that the sensitivity of the simplex PCR targeting XEA5 marker is ten-fold higher than the multiplex PCR. The detection limit of 0.1 ng/µL attained for the multiplex PCR is similar to what has been reported in other studies (0.02 and 0.5 ng/µL) [40,41].…”
Section: Discussionsupporting
confidence: 89%
“…This conveys a sense of continuing excitement in the field of molecular plant pathology to control bacterial rice pathogens. To date, the main approaches to control bacterial rice pathogens include the production of disease-resistant rice varieties [ 34 , 35 , 36 ]; modification in cultural practices [ 37 , 38 ]; use of natural products or botanical extracts [ 39 , 40 , 41 ]; use of conventional and non-conventional chemicals [ 42 , 43 ]; coevolution analysis of the pathogen virulence and the host resistance genes [ 44 , 45 ]; transcriptomic analysis of pathogen along rice development [ 46 , 47 ]; improvement of diagnostic tools in the field for early detection of infectious diseases [ 48 ].…”
Section: Bacterial Rice Pathogensmentioning
confidence: 99%
“…All three remained rare, with only one sample containing each of these sequences. The presence of B. glumae was described in Burkina Faso (but with no molecular data; Ouedraogo et al 2004), and targeted detection performed in two sites failed to detect B. glumae and A. avenae (Bangratz et al 2020). For fungal pathogens, we found ASVs assigned to ten genera comprising rice pathogens, including Bipolaris, Curvularia, Fusarium and Rhizoctonia.…”
Section: Identification Of Core Microbiota and Hub Phylotypesmentioning
confidence: 58%